Secretome weaponries of Cochliobolus lunatus interacting with potato leaf at different temperature regimes reveal a CL[xxxx]LHM - motif - Louis, Bengyella (BioMed Central, 2014)
BACKGROUND: Plant and animal pathogenic fungus Cochliobolus lunatus cause great economic damages worldwide every year. C. lunatus displays an increased temperature dependent-virulence to a wide range of hosts. Nonetheless, this phenomenon is poorly understood due to lack of insights on the coordinated secretome weaponries produced by C. lunatus under heat-stress conditions on putative hosts. To understand the mechanism better, we dissected the secretome of C. lunatus interacting with potato (Solanum tuberosum L.) leaf at different temperature regimes. RESULTS: C. lunatus produced melanized colonizing hyphae in and on potato leaf, finely modulated the ambient pH as a function of temperature and secreted diverse set of proteins. Using two dimensional gel electrophoresis (2-D) and mass spectrometry (MS) technology, we observed discrete secretomes at 20°C, 28°C and 38°C. A total of 21 differentially expressed peptide spots and 10 unique peptide spots (that did not align on the gels) matched with 28 unique protein models predicted from C. lunatus m118 v.2 genome peptides. Furthermore, C. lunatus secreted peptides via classical and non-classical pathways related to virulence, proteolysis, nucleic acid metabolism, carbohydrate metabolism, heat stress, signal trafficking and some with unidentified catalytic domains. CONCLUSIONS: We have identified a set of 5 soluble candidate effectors of unknown function from C. lunatus secretome weaponries against potato crop at different temperature regimes. Our findings demonstrate that C. lunatus has a repertoire of signature secretome which mediates thermo-pathogenicity and share a leucine rich “CL[xxxx]LHM”-motif. Considering the rapidly evolving temperature dependent-virulence and host diversity of C. lunatus, this data will be useful for designing new protection strategies.